VIP and Calcitonin-Producing Pancreatic Neuroendocrine Tumor with Watery Diarrhea: Clinicopathological Features and the Effect of Somatostatin Analogue - Kon, Tomoya; Wada, Ryuichi; Suzuki, Ryuta; Nakayama, Yoshihito; Ebina, Yoshihito; Yagihashi, Soroku (JOP. Journal of the Pancreas, 2012)
Context Pancreatic neuroendocrine tumor (pNET) secretes various peptide hormones; however, calcitonin hypersecretion is rare. Its clinicopathological significance and treatment is still controversial. Case report A 43 year-old Japanese man presented severe watery diarrhea and a large mass in the pancreatic tail. Blood concentration of VIP was elevated to 649 pg/mL (reference range: 0-100 pg/mL), and calcitonin to 66,700 pg/mL (reference range: 15-86 pg/mL). There was no tumor in other endocrine organs. The resected tumor was composed of 80% calcitonin-positive cells and 10% VIP-positive cells. After the operation, the levels of VIP and calcitonin were decreased to 44 and 553 pg/mL, respectively, and diarrhea was improved. The mRNA of somatostatin receptor (SSTR) subtypes 2, 3 and 5 in the tumor tissue were increased 22.8, 25.1, and 37.0-fold of those of normal pancreas, respectively. At 19 months after the operation, blood calcitonin was again raised to 3,980 pg/mL, and metastatic tumors were found in the liver. With the treatment of long-acting somatostatin analogue, calcitonin was reduced to 803 pg/mL. The patient does not present endocrine symptom, and the size of the metastatic tumors appears stable. Conclusion From the world literature to date, co-secretion of VIP and calcitonin was documented in only 10 cases of pNET including the current case. Although VIP is a primary cause of diarrhea in these cases, high level of calcitonin may also influence on the clinical symptoms. Somatostatin analogue suppresses the levels of VIP and calcitonin, and the control proliferation is also expected when tumor cells express SSTRs.